2016
DOI: 10.1103/physrevb.93.245140
|View full text |Cite
|
Sign up to set email alerts
|

Edge theory approach to topological entanglement entropy, mutual information, and entanglement negativity in Chern-Simons theories

Abstract: We develop an approach based on edge theories to calculate the entanglement entropy and related quantities in (2+1)-dimensional topologically ordered phases. Our approach is complementary to, e.g., the existing methods using replica trick and Witten's method of surgery, and applies to a generic spatial manifold of genus g, which can be bipartitioned in an arbitrary way. The effects of fusion and braiding of Wilson lines can be also straightforwardly studied within our framework. By considering a generic superp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(141 citation statements)
references
References 48 publications
11
123
0
Order By: Relevance
“…Our method applies to a Chern-Simons gauge theory defined on an arbitrary oriented (2+1)-dimensional spacetime manifold. Our results agree with the edge theory approach in a recent work [35]. …”
supporting
confidence: 82%
See 1 more Smart Citation
“…Our method applies to a Chern-Simons gauge theory defined on an arbitrary oriented (2+1)-dimensional spacetime manifold. Our results agree with the edge theory approach in a recent work [35]. …”
supporting
confidence: 82%
“…Recently, the entanglement negativity has been extensively studied in conformal field theories [11][12][13], quantum spin chain systems [14][15][16][17][18][19][20], coupled harmonic oscillators in one and two dimensions [21][22][23][24][25][26][27], free fermion systems [28][29][30][31][32], topological ordered systems [33][34][35], and holographic entanglement [36][37][38]. Furthermore, the entanglement negativity has JHEP09(2016)012 also been studied in the non-equilibrium case [39][40][41][42] as well as the finite temperature case [39,43,44].…”
Section: Jhep09(2016)012mentioning
confidence: 99%
“…Modular invariance dictates that |B satisfies the Cardy condition, which implies that |B is a particular linear combination of the Ishibashi states, with the coefficients given by elements of the modular S-matrix. Unfortunately, the state |B does not reproduce the known entanglement entropies in Chern Simons theory, and the authors of [89] showed how to obtain the correct entropies by relaxing the Cardy condition.…”
Section: Entanglement Edge Modes and Topological Phasesmentioning
confidence: 99%
“…The appearance of physical edge modes in the entanglement spectrum of topological phases was first discussed in [65], [82], [70] and the computation of topological entanglement entropy in terms of left-right entanglement of boundary states was done in [22]. The reference [89], noted a problem with the approach of [70], where the reduced density matrix was obtained by a quantum quench in which region A and B are disconnected suddenly. The initial condition for such a quench is given by a conformally invariant boundary state |B satisfying…”
Section: Entanglement Edge Modes and Topological Phasesmentioning
confidence: 99%
See 1 more Smart Citation